Efficacy of capnographic and bispectral index monitoring on trans‐oral therapeutic endoscopy: A prospective observational study. Issue 10 (8th July 2022) - Hayashi, Yukie; Hosoe, Naoki; Takabayashi, Kaoru; Limpias Kamiya, Kenji J. L.; Tojo, Anna; Sakurai, Hinako; Kinoshita, Satoshi; Sujino, Tomohisa; Nakayama, Atsushi; Kato, Motohiko; Yahagi, Naohisa; Ogata, Haruhiko; et al.
Abstract: Background and Aim: Oral therapeutic and invasive endoscopy requires deep sedation to reduce patient distress due to prolonged examination and procedures. The usefulness of capnography and bispectral index (BIS) monitoring in the early hypoxia detection in oral therapeutic and invasive endoscopy has yet to be evaluated. This study aimed to investigate the clinical impact of capnography and BIS monitoring on hypoxic events during oral therapeutic and invasive endoscopic procedures. Methods: This is a prospective observational study. Trans‐oral non‐intubated therapeutic and/or invasive endoscopic procedures were performed with conventional monitoring (pulse oximetry, pulse, and blood pressure) as well as additional monitoring (BIS and end‐tidal CO2 concentration). Hypoxia is defined as oxygen saturation of <90% that lasts >15 s. The clinical impact of capnography and BIS monitoring on hypoxic events during oral therapeutic and invasive endoscopic procedures were investigated with the risk factors for hypoxia in each patient. Results: Patients with hypoxia had significantly more apneas detected using capnography than other patients. The multivariate analysis revealed the detected apnea by capnography as an independent risk factor for hypoxia (odds ratio: 3.48[95% confidence interval: 1.24–9.78], P  = 0.02). The BIS was not significantly different as a risk factor for hypoxia; however, per‐event analysis revealed significantly decreased BIS values over time in 3 min before hypoxic events. Conclusions: Apnea detected by capnography was an independent predictor of hypoxia. The BIS value was not associated with hypoxia events; however, it showed a significant downward trend before hypoxia events.